PENGARUH BRAND AMBASSADOR IKATAN CINTA TERHADAP KECERDASAN SPASIAL DALAM MEMBUAT KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE OLEH REMAJA DI JAWA TIMUR - Inggrit Aulia Wati Hasanah; Arrum Wizarotul Maliyah; Naufal Alif Kusuma Wardhana; Adrian Maulana Dahlan; Dwi Yuli Rakhmawati (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
This study aims to determine the effect of the brand ambassador of the Ikatan Cinta Association in East Java on the Shopee marketplace with spatial intelligence variables in purchasing decisions, psychological factors, and Ikatan Cinta player interactions. Sampling in this study used a sampling method using google form. The number of samples used using the Kerlinger and Lee approach as many as 30 respondents. Data analysis used multiple linear analysis with SPSS version 20. The results of this study indicate that the brand ambassador of the Ikatan Cinta consisting of spatial intelligence variables in making purchasing decisions, psychological factors, and regression of Ikatan Cinta, has a negative effect on purchasing decisions in the Shopee marketplace.